RESEARCH METHODS FOR OPTIMAL DECISION MAKING UNDER THE CONTROL OF AVIATION TECHNICAL OPERATION - Богайська, К.В. (Science-based technologies, 2013)
It is proposed and studied mechanisms of decision-making that allow exactly or approximately to implement random function selection. The proposed models can be used for extrapolating behavior of such complex systems as aircraft